Three new species of Papuagrion Ris, 1913 (Odonata: Coenagrionidae) from the Hindenburg Wall region of western Papua New Guinea - Orr, A.g.; Richards, S.j. (Zootaxa, 2016)
Three distinctive new species of Papuagrion Ris, 1913 are described from a high altitude area (1,770–1,820 m a.s.l.) at the base of the Hindenburg Wall, Western Province, Papua New Guinea. These are P. chrysosoma sp. nov., P marijanmatoki sp. nov. and P. tydecksjuerging sp. nov.; all type material is deposited in the South Australian Museum (SAMA). These were the only species of the genus collected at higher altitudes in the Ok Tedi headwaters, and none of them were encountered at lower altitudes (300–900 m) despite intensive searches there. The new species described here bring to 26 the number of Papuagrion species known from the New Guinea region.